2007
DOI: 10.1128/aem.02201-06
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Physiological Characterization of Saccharomyces boulardii , the Probiotic Strain of Saccharomyces cerevisiae

Abstract: Saccharomyces boulardii, a yeast that was isolated from fruit in Indochina, has been used as a remedy for diarrhea since 1950 and is now a commercially available treatment throughout Europe, Africa, and South America. Though initially classified as a separate species of Saccharomyces, recent publications have shown that the genome of S. boulardii is so similar to Saccharomyces cerevisiae that the two should be classified as conspecific. This raises the question of the distinguishing molecular and phenotypic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
157
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(171 citation statements)
references
References 63 publications
10
157
0
4
Order By: Relevance
“…Higher optimal growth temperature (~37 °C) Lower optimal growth temperature (~30 °C) Higher resistance to low pH [11] Lower resistance to low pH [11] The karyotypes of Sb are very similar to those of S. cerevisiae…”
Section: Sb S Cerevisiaementioning
confidence: 80%
See 4 more Smart Citations
“…Higher optimal growth temperature (~37 °C) Lower optimal growth temperature (~30 °C) Higher resistance to low pH [11] Lower resistance to low pH [11] The karyotypes of Sb are very similar to those of S. cerevisiae…”
Section: Sb S Cerevisiaementioning
confidence: 80%
“…It has been shown that yeast pathogenicity correlates with survival in oxidative stress [20] which could be triggered by transcription factor Rds2 [21] or activation of MAP kinases and variability in the polyglutamine tract of Slt2 [22]. Probiotic properties are also strain specific, which is the case for Sb used as probiotic [11,12]. Thus there is a need for a valuable molecular markers able to distinguish among strains and establish appropriate methods for the identification of probiotic strains of the Sb.…”
Section: Systematic Classificationmentioning
confidence: 99%
See 3 more Smart Citations